SEMIoTICA - Security Scenarios Modeling for IoT-based Agriculture Solutions - Hurtado, Julio Ariel (2023)
Agriculture is a vital human activity contributing to sustainable development. A few decades ago, the agricultural sector introduced the Internet of Things (IoT), playing a relevant role in precision and smart farming. IoT developments in farms require a lot of connected devices working cooperatively. It increases the vulnerability of IoT devices mostly because it lacks the necessary built-in security due to their constrained context and computational capacity. Additionally, storage and data processing connecting with edge or cloud servers are the reason for many security threats. To ensure that IoT-based solutions meet functional and non-functional requirements, particularly security, software companies should adopt a security-focused approach to their specification. This paper proposes a method for specifying security scenarios integrating requirements and architecture viewpoints in the context of the IoT in agriculture solutions. The method comprises four activities. First, the description of scenarios for the intended software. After that, scenarios with incorrect system use should be described. Then, these are translated into security scenarios using a set of rules. Finally, the security scenarios are improved. Additionally, this paper describes a preliminary validation of the approach, which software engineers in Argentina and Colombia performed. The results show that the approach proposed allows software engineers to define and analyze security scenarios in the IoT and agriculture contexts with good results.